Tranexamic Acid (TXA) in Trauma Patients: Barriers to Use among Trauma Surgeons and Emergency Physicians - Abdulaziz Alburaih (Emergency Medicine International)
Objective. Tranexamic Acid (TXA) is currently the only drug with prospective clinical evidence supporting its use in bleeding trauma patients. We sought to better understand the barriers preventing its use and elicit suggestions to further its use in trauma patients in the state of Maryland. Methods. This is a cross-sectional study. Results. The overall response rate was 38%. Half of all participants reported being familiar with the CRASH-2 trial and MATTERs study. Half reported being aware of TXA as part of their institution’s massive transfusion protocol. The majority of participants felt that TXA would have a significant positive impact on the survival of trauma patients. A majority also felt that the use of TXA would increase if its administration was the responsibility of both trauma surgeons and emergency physicians. Conclusion. Only half of responders reported being aware of TXA as being part of their institution’s massive transfusion protocol. Lack of awareness of the clinical data supporting its use is a major barrier. However, most trauma providers and emergency physicians do have a favorable view of TXA and support its incorporation into massive transfusion protocols. We believe that more studies of this kind on both state and national level are needed.